(untitled) (Afaq Lughawiyyah, 2024)
This study explores the influence of Islamic themes and approaches in Arabic poetry in the city of Osogbo, Nigeria. It focuses on three prominent poets: Imam Abdul Latif Muhammad, Saeed Ismail Alabi and Abdul Hameed Abdul Raheem. The research aims to highlight how these poets incorporate Islamic themes and values into their literary works. The study provides a historical context of Islamic scholarship and Arabic poetry in Nigeria, emphasizing the development and impact of these artistic traditions in Osogbo. Historical and Descriptive methods were adopted in this study, while comprehensive discourse analysis is used in appraising all the artistic values of the selected poems critically. Through a detailed analysis of selected poems, the research examines the stylistic features and recurring religious themes in the poets’ works. The study concludes that Islamic poetry in Osogbo plays a crucial role in preserving and promoting Islamic culture through Arabic literature.